Self-perceived employability, organization-rated potential, and the psychological contract. Issue 5 (8th July 2014) - Dries, Nicky; Forrier, Anneleen; De Vos, Ans; Pepermans, Roland
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to study the relationship between self-perceived employability resources and perceived psychological contract (PC) obligations. To examine the extent to which organizational ratings of potential, through their "signaling" function, might serve as a buffer between employability and PC perceptions that are undesirable from an employer's point of view. Design/methodology/approach – Both self-report data (i.e. self-perceived employability resources and perceived PC obligations) and data reported by the HR departments of the participating organizations (i.e. organizational ratings of potential) were collected in a case-control design (n=103). Findings – Self-perceived employability resources are not related to lower intentions to stay with one's current employer. High-potential employees did not perceive themselves as particularly obliged to reciprocate their organizations' additional investments in them by expressing longer term loyalty, or a higher performance level. Practical implications – Organizations should not be hesitant to assist their employees in enhancing their employability resources. In addition, they should engage in deliberate PC building with their high-potential employees so as to align their perceived PC obligations with the organizational agenda. Originality/value – The relationship between self-perceived employability resources and perceived PC obligations has been underexamined; hardly any PC research has taken organizational variables into account; hardly any research exists on the psychological implications of being identified as a high potential; and the study draws both on self-report data and data reported by the HR departments of the participating organizations.